Kinematic Modeling and Simulation of a 2-R Robot by Using Solid Works and Verification by MATLAB/Simulink - Fernini Brahim (IAES International Journal of Robotics and Automation (IJRA), 2012)
Simulation of robot systems which is getting very popular, especially with the lowering cost of computers, can be used for layout evaluation, feasibility studies, presentations with animation and off-line programming. Object staging modelisation using robots holds, wether for the object or the robot, the following models: The geometric one, the kinematics one and the dynamic one. To do so, the modelisation of a 2-R robot type is being implemented. Comparing between two robot postures with the same trajectory (path) and for the same length of time and establishing a computing code to obtain the kinematic and dynamic parameters are the main tasks. SolidWorks and Matlab/Simulink softwares are used to check the theory and the robot motion simulation. The verification of the obtained results by both softwares allows us to, qualitatively evaluate ,underline the rightness of the chosen model and to get the right conclusions. The results of simulations were discussed. An agreement between the two softwares is certainly Obtained.DOI: http://dx.doi.org/10.11591/ijra.v1i2.350